A nationally representative study of law enforcement shiftwork and health outcomes. Issue 4 (4th May 2021) - Mumford, Elizabeth A.; Maitra, Poulami; Liu, Weiwei; Taylor, Bruce G.
Abstract: The purpose of this study was to estimate the effect of past and current rotating shift assignments on U.S. law enforcement officers' health outcomes. In a nationally representative sample of 2, 867 officers, with an oversample of female officers, we estimated models of sleep quality and fatigue, physical health outcomes, and psychological health outcomes. Further, we examined individual and agency-level factors associated with officers who reported currently working a rotating shift, to investigate what patterns there may be in shift assignments. A history of rotating shift assignments was positively associated with lower sleep quality, and with hypertension, diabetes, and high cholesterol, but not with gastrointestinal disorders, perceived stress, emotional well-being, or suicidality. The associations of shiftwork with health outcomes did not vary by gender. Demographic characteristics did not predict current rotating shift assignments, but a longer history of shiftwork and more working hours did predict a current shift assignment. Attention to mitigating shift system designs as well as the effect of cumulative years of working a rotating shift for the benefit of officer health outcomes is warranted.